1988
DOI: 10.1111/j.1745-3984.1988.tb00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Improving the Reliability of the GPA on Prediction Generally and on Comparative Predictions for Gender and Race Particularly

Abstract: The reliability of a method of adjusting grade point averages for differences in departmental grading standards was examined, as were the effects of such adjustments on the predictive validity of high school grades, SAT scores, and achievement test scores. The index of differential grading standards for all on-time graduates of the Dartmouth College class of 1986 was quite reliable, and its use in adjusting grade averages increased predictive validity, reduced its erosion over years, reduced the apparent under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
3

Year Published

1991
1991
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(109 citation statements)
references
References 15 publications
8
98
3
Order By: Relevance
“…For example, in analyses of combined Latino American and non-Latino white groups, Pennock-Roman (1990, Table 3.15) found that humanities, social sciences, business, and education majors were more leniently graded 14 than physical sciences and engineering majors at all six institutions studied, but the biological/health sciences showed less consistent results. The findings from the present investigation and Pennock-Roman (1990) are consistent with many studies that have shown large contrasts in grading leniency between quantitative and nonquantitative majors (Elliott and Strenta 1988;Goldman. and Hewitt 1975;Goldman er al, 1974).…”
Section: Effectiveness Of College Majors As a Control For Grading Lensupporting
confidence: 92%
See 4 more Smart Citations
“…For example, in analyses of combined Latino American and non-Latino white groups, Pennock-Roman (1990, Table 3.15) found that humanities, social sciences, business, and education majors were more leniently graded 14 than physical sciences and engineering majors at all six institutions studied, but the biological/health sciences showed less consistent results. The findings from the present investigation and Pennock-Roman (1990) are consistent with many studies that have shown large contrasts in grading leniency between quantitative and nonquantitative majors (Elliott and Strenta 1988;Goldman. and Hewitt 1975;Goldman er al, 1974).…”
Section: Effectiveness Of College Majors As a Control For Grading Lensupporting
confidence: 92%
“…The categorization of majors used here apparently had no greater advantage in reducing gender differences as compared with the dummy-variable approach to the coding of majors into four broad categories used in the earlier analyses (Pennock-Roman 1990). The evidence from several studies (Elliott and Strenta 1988;Goldman and Hewitt 1975;Goldman et a!. 1974;Pennock-Roman 1990) suggests that the most important distinction to make is that between quantitative and nonquantitative majors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations